Disruption of the Dimer-Dimer Interaction of the Mumps Virus Attachment Protein Head Domain, Aided by an Anion Located at the Interface, Compromises Membrane Fusion Triggering - Kubota, Marie (J Virol, 2020)
Mumps virus (MuV), an enveloped negative-strand RNA virus belonging to the family Paramyxoviridae, enters the host cell through membrane fusion mediated by two viral envelope proteins, an attachment protein hemagglutinin-neuraminidase (MuV-HN) and a fusion (F) protein. However, how the binding of MuV-HN to glycan receptors triggers membrane fusion is not well understood. The crystal structure of the MuV-HN head domain forms a tetramer (dimer of dimers) like other paramyxovirus attachment proteins. In the structure, a sulfate ion (SO(4)(2−)) was found at the interface between two dimers, which may be replaced by a hydrogen phosphate ion (HPO(4)(2−)) under physiological conditions. The anion is captured by the side chain of a positively charged arginine residue at position 139 of one monomer each from both dimers. Substitution of alanine or lysine for arginine at this position compromised the fusion support activity of MuV-HN without affecting its cell surface expression, glycan-receptor binding, and interaction with the F protein. Furthermore, the substitution appeared to affect the tetramer formation of the head domain as revealed by blue native-PAGE analysis. These results, together with our previous similar findings with the measles virus attachment protein head domain, suggest that the dimer-dimer interaction within the tetramer may play an important role in triggering membrane fusion during paramyxovirus entry. IMPORTANCE Despite the use of effective live vaccines, mumps outbreaks still occur worldwide. Mumps virus (MuV) infection typically causes flu-like symptoms and parotid gland swelling but sometimes leads to orchitis, oophoritis, and neurological complications, such as meningitis, encephalitis, and deafness. MuV enters the host cell through membrane fusion mediated by two viral proteins, a receptor-binding attachment protein, and a fusion protein, but its detailed mechanism is not fully understood. In this study, we show that the tetramer (dimer of dimers) formation of the MuV attachment protein head domain is supported by an anion located at the interface between two dimers and that the dimer-dimer interaction plays an important role in triggering the activation of the fusion protein and causing membrane fusion. These results not only further our understanding of MuV entry but provide useful information about a possible target for antiviral drugs.